2015
DOI: 10.1038/jhh.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of elevated blood pressure and associated risk factors in Chinese children: the SNEC study

Abstract: Despite the association of childhood blood pressure (BP) with hypertension later in the life course, there remains dearth of information regarding the prevalence and emergence of hypertension in children, especially in China. To investigate the current status of BP, prevalence of elevated BP and related factors in Chinese children, a cross-sectional survey in a representative sample of 9354 Chinese children 5-17 years old was conducted in seven cities in Northeastern China during 2011 and 2012. BP measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…It has always been of interest to explore the association between LBW and later HBP, and the results of previous studies are varied. One study conducted in Jerusalem found that LBW had little influence on blood pressure in adolescents aged 17 [16], while another study found being born small for one’s gestational age may be a predictor of raised blood pressure when an individual is in their early 30s [24]. Both conclusions were supported by numbers found in later studies [25,26,27,28].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has always been of interest to explore the association between LBW and later HBP, and the results of previous studies are varied. One study conducted in Jerusalem found that LBW had little influence on blood pressure in adolescents aged 17 [16], while another study found being born small for one’s gestational age may be a predictor of raised blood pressure when an individual is in their early 30s [24]. Both conclusions were supported by numbers found in later studies [25,26,27,28].…”
Section: Discussionmentioning
confidence: 92%
“…However, some studies have showed little effect of LBW on blood pressure in young adults [9,10]. On the other hand, some recent studies suggest that the co-existence of low birthweight and later obesity, rather than low birthweight itself, was a strong risk factor of HBP during adolescence [11,12,13,14,15,16,17]. The relationship between LWB and HBP remains unclear, and obesity during school-age is seldom brought into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have reported an increased risk of childhood-onset primary (essential) hypertension in low birth weight infants (Edvardsson, Steinthorsdottir, Eliasdottir, Indridason, & Palsson, 2012; R. R. Huxley, Shiell, & Law, 2000; Mu et al, 2012; Zhou et al, 2015), possibly due to alterations in their renal or vascular systems related to reduced growth in utero (Barker, Bagby, & Hanson, 2006; Edvardsson et al, 2012; Hughson, Farris, Douglas-Denton, Hoy, & Bertram, 2003; Kaplan, 2014; Norman, 2008). Less clear however, is whether high birth weight, which may have long-term adverse metabolic effects, such as insulin resistance (Darendeliler et al, 2009; Mandy, 2014), is also a risk factor for the development of primary hypertension in childhood (Edvardsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure (HBP) is increasing in prevalence among children and youth, and there is evidence that HBP is present in Chinese children as young as 5 years old 1 .…”
Section: Introductionmentioning
confidence: 99%